A regenerated natural polymer-based solid-solid phase change fiber and its preparation method and application

By incorporating regenerated natural polymer-based solid-solid-phase change fibers into the asphalt, the ambient temperature is adjusted using the latent thermal characteristics of the fibers, the softening problem of asphalt pavement in high temperature environments is solved, the temperature stability and service life are improved, and environmentally friendly and sustainable modified asphalt process is realized.

CN118127653BActive Publication Date: 2025-03-18CHANGAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410309696.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-19
Publication Date
2025-03-18
Estimated Expiration
2044-03-19

AI Technical Summary

Technical Problem

The existing asphalt pavement is prone to softening in high temperature environments, resulting in shortening of ruts and service life. The traditional modified asphalt process is complex and costly, and the modifier may pollute the environment and affect the adhesion and durability of the asphalt.

Method used

Regenerated natural polymer-based solid-solid phase change fibers are used to prepare fibers with phase change function through chemical grafting reaction between natural polymer materials and phase change materials, and fibers are prepared by solution spinning method, added to asphalt to modify the asphalt, and the ambient temperature is adjusted using the latent thermal characteristics of the fibers.

Benefits of technology

It improves the temperature stability of asphalt, reduces the risk of rutting caused by high temperature on the road surface, extends the service life of asphalt pavement, and reduces production and maintenance costs. The modifier is environmentally friendly and sustainable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118127653B_ABST
    Figure CN118127653B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of modified asphalt, and specifically relates to a regenerated natural polymer-based solid-solid phase change fiber and its preparation method and application. The present invention uses natural polymer materials as raw materials, obtains natural polymer-based solid-solid phase change materials by chemical grafting with phase change materials, and obtains regenerated natural polymer-based solid-solid phase change fibers by solution spinning. Phase change materials have latent heat properties and can store heat and regulate temperature. Phase change fibers are added to asphalt. When the ambient temperature rises to its phase change temperature, the phase change fibers absorb a large amount of heat and store it, improving the high temperature stability and durability of asphalt and asphalt mixtures, and can reduce high temperature diseases of the road surface while improving road performance; when the ambient temperature drops to its phase change temperature, the phase change fibers release a large amount of heat, improve the low temperature resistance and low temperature stability of the road surface, reduce low temperature cracks, and improve the temperature stability of asphalt through phase change fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of modified asphalt, and specifically relates to a regenerated natural polymer-based solid-solid phase change fiber and a preparation method and application thereof. Background Art

[0002] Asphalt pavement is an important part of the transportation system. As a black material, asphalt has a strong ability to absorb heat and easily causes high temperatures on the road surface, especially in summer. Temperature is an important factor affecting the performance and service life of asphalt pavement. For example, high road temperature softens asphalt, and heavy vehicles are at great risk of rutting due to plastic deformation, which reduces the smoothness of the road surface and affects traffic safety. At the same time, high road temperature will increase the urban heat island effect. With global warming, the problem of high road temperature will become more serious, so it is crucial to control the temperature of asphalt pavement.

[0003] At present, the main treatment methods for temperature diseases of asphalt pavement are traditional modified asphalt and reflective heat-insulating coatings. On the one hand, the production process of traditional modified asphalt uses a lot of additives, the process is relatively complex, and the mastery and promotion of the technology is much more difficult. The manufacturing process needs to be optimized and improved to better ensure its quality and performance, and the production and maintenance costs are high. On the other hand, some modifiers will not only pollute the environment when used, but also pose a safety hazard to construction, and will also affect the adhesion and durability of asphalt materials, causing "segregation" of asphalt during transportation, accelerating the aging of asphalt, and thus reducing the service life of the pavement. In fact, modified asphalt generally improves its temperature stability by reducing or mitigating the adverse effects caused by changes in external temperature.

[0004] In the existing fiber-modified asphalt technology, the fiber materials used generally include basalt fiber, glass fiber, wood fiber, polyester fiber and carbon fiber, etc., which mainly play the role of blocking, reinforcement and toughening to inhibit the further expansion of pavement cracks. However, these fibers can generally only improve the ability to resist temperature changes under corresponding ambient temperature conditions, and cannot play a role in regulating the ambient temperature. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a regenerated natural polymer-based solid-solid phase change fiber and a preparation method and application thereof. The present invention incorporates phase change fibers into asphalt, which can not only play a role in reinforcement and toughening, but also utilize the latent heat characteristics of the phase change fibers to absorb or release heat under corresponding environmental conditions, and regulate the temperature of the environment, thereby further improving the temperature stability of the asphalt.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A regenerated natural polymer-based solid-solid phase change fiber is based on a natural polymer material, and the natural polymer-based solid-solid phase change material is obtained by chemically grafting the hydroxyl groups on the natural polymer material with the phase change material, and then the natural polymer-based solid-solid phase change material is spun by a solution spinning method to obtain a regenerated natural polymer-based solid-solid phase change fiber;

[0008] The phase change material is a phase change material having a single functional group;

[0009] Wherein, the monofunctional phase change material is selected from one or more of modified polyethylene glycol, octadecyl acrylate, homologues of octadecyl acrylate, octadecylamine, and oleylamine;

[0010] The homologue of octadecyl acrylate is selected from lauryl acrylate or pentadecyl methacrylate, and in the phase change material having a single functional group, the functional group can react with the hydroxyl group on the natural polymer material.

[0011] Preferably, the modified polyethylene glycol is selected from polyethylene glycol monomethyl ether methacrylate, methoxy polyethylene glycol-hydroxyl (PEG-OH), methoxy polyethylene glycol-aldehyde (PEG-CHO) or methoxy polyethylene glycol isocyanate (PEG-CNO).

[0012] Preferably, the natural polymer material is selected from cellulose, chitosan, lignin or chitin. The present application provides methods for preparing natural polymer-based solid-solid phase change materials using these four materials as raw materials.

[0013] Preferably, the natural polymer-based solid-solid phase change material is a comb-like structure polymer, and the natural polymer-based solid-solid phase change material can be dissolved by imidazole-type ionic liquids to prepare spinning fibers. The natural polymer material is a long-chain structure with several active hydroxyl groups. The main chain is equivalent to the "comb handle". Only a single functional group of the phase change material can react with the active hydroxyl groups of the natural polymer material to form a sub-chain, which is equivalent to the "comb teeth", and finally a comb-like structure; the sub-chains of this structure are not cross-linked, so the polymer as a whole can be dissolved by the ionic liquid, and the target phase change fiber can be obtained by spinning.

[0014] Preferably, the natural polymer-based solid-solid phase change material is prepared according to the following steps:

[0015] Cellulose, lignin and chitin are modified respectively to obtain processed natural polymer material I; natural polymer materials themselves have some limitations, such as poor solubility and difficult processing, etc. After modification, their solubility and activity are improved, which is convenient for subsequent reactions;

[0016] The treated natural polymer material I, the phase change material and the initiator are mixed, and the treated natural polymer material I and the phase change material are used as raw materials. Then, a free radical polymerization reaction is carried out under completely anaerobic conditions to obtain the natural polymer-based solid-solid phase change material I. Under the action of the initiator, the phase change material is grafted onto the treated natural polymer material I through free radical polymerization. When the phase change material is selected from polyethylene glycol monomethyl ether methacrylate, the hydroxyl group on the treated natural polymer material I reacts with the acrylate group on the phase change material. The specific reaction is shown in FIG. Figure 2 ; Benzoyl peroxide initiator decomposes under heating conditions to produce free radicals, thereby initiating monomer polymerization. Methyl ethyl ketone peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide also have similar effects; Octadecyl acrylate is a phase change material, and the phase change temperature decreases with the decrease of carbon chain length. Dodecyl acrylate, pentadecyl methacrylate, etc. can also be used as phase change materials for this application. In addition, octadecylamine, oleylamine and other phase change materials with single functional groups can also be used. In single functional group phase change materials, only the end functional groups can react with the active hydroxyl groups in natural polymer materials to generate sub-chains, and the sub-chains are not cross-linked with each other to form a comb-like structure.

[0017] Preferably, the mass ratio of the treated natural polymer material I, the phase change material, and the initiator is 0.1-0.2:1-2:0.06.

[0018] Preferably, the natural polymer-based solid-solid phase change material is prepared according to the following steps:

[0019] The chitosan is modified to obtain a processed natural polymer material II;

[0020] The treated natural polymer material II, the phase change material and the cross-linking agent glutaraldehyde are mixed, left to stand for 5-7 hours and then dried. During the standing process, the two aldehyde groups of the glutaraldehyde molecule react with the hydroxyl group on the treated natural polymer material II and the active group on the phase change material, respectively, thereby connecting the two to obtain a natural polymer-based solid-solid phase change material II; the main purpose of glutaraldehyde as a cross-linking agent is to graft the phase change material onto the treated natural polymer material II;

[0021] The ratio of the treated natural polymer material II, phase change material and glutaraldehyde is 1-1.2g:5-10g:1-2mL, one aldehyde group of the glutaraldehyde molecule reacts with the active hydroxyl group of the natural polymer material, and the other aldehyde group reacts with the terminal functional group of the phase change material, thereby connecting the natural polymer material and the phase change material, and the treated natural polymer material II is 0.025g / mL.

[0022] The present invention also protects a method for preparing the above-mentioned regenerated natural polymer-based solid-solid phase change fiber, which comprises dissolving the natural polymer-based solid-solid phase change material I or the natural polymer-based solid-solid phase change material II in an imidazole-type ionic liquid, and then performing electrostatic spinning to obtain the regenerated natural polymer-based solid-solid phase change fiber.

[0023] Preferably, the imidazolium-type ionic liquid is selected from 1-butyl 3-methylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium chloride or 1-butylchloro-3-methylimidazolium chloride.

[0024] Preferably, the length of the regenerated natural polymer-based solid-solid phase change fiber is 0.01-3 mm, and the diameter is 10-100 μm. The obtained regenerated natural polymer-based solid-solid phase change fiber is finally subjected to vacuum drying treatment at 100-110° C. for 2-3 hours.

[0025] Preferably, the cellulose modification treatment method is: cellulose and acryloyl chloride are co-dispersed in N, N-dimethylacetamide, part of the hydroxyl groups in the cellulose react with acryloyl chloride to form acryloyl groups for grafting with the phase change material, and after the reaction is completed, the cellulose is washed and soaked with anhydrous ethanol to remove the residual solvent and organic impurities to obtain cellulose acrylate. The reaction formula is shown in the attached Figure 1 Specifically, 1 g of cellulose was added with 50 ml of solvent N, N-dimethylacetamide (DMAC) and 10 ml of acryloyl chloride (AC) and stirred for 5 h. After the reaction, the mixture was washed and soaked with anhydrous ethanol, and filtered and dried to obtain cellulose acrylate.

[0026] The modification treatment method of chitosan is: dispersing chitosan in an acetic acid solution with a volume fraction of 0.5%; specifically: taking 0.25g of chitosan, adding it to the acetic acid solution with a volume fraction of 0.5%, stirring it in a water bath at 25°C for 2h, ultrasonically treating the mixed solution for 30min to remove bubbles generated during the stirring process, and then standing it for 1h to obtain a uniform and stable chitosan acetic acid solution with a concentration of 0.025g / ml;

[0027] The modification treatment method of lignin is as follows: lignin and acryloyl chloride are co-dispersed in N,N-dimethylacetamide, part of the hydroxyl groups in the lignin react with acryloyl chloride to form acryloyl groups for grafting with phase change materials, and after the reaction, the lignin is washed and soaked with anhydrous ethanol to obtain lignin acrylate; the reaction formula is shown in the attached Figure 1 ; Specifically: take 1g of lignin, add 50ml of solvent N,N-dimethylacetamide (DMAC) and 10ml of acryloyl chloride (AC) and stir for 5h, wash and soak with anhydrous ethanol after the reaction, and filter and dry to obtain lignin acrylate;

[0028] The modification treatment method of chitosan is as follows: chitosan and acryloyl chloride are co-dispersed in N,N-dimethylacetamide, part of the hydroxyl groups in chitosan react with acryloyl chloride to form acryloyl groups for grafting with phase change materials, and after the reaction, the chitosan is washed and soaked with anhydrous ethanol to obtain chitosan acrylate; the reaction formula is shown in the attached Figure 1 Specifically, 1g of chitosan was added with 50ml solvent N,N-dimethylacetamide (DMAC) and 10ml acryloyl chloride (AC) and stirred for 5h. After the reaction, the mixture was washed and soaked with anhydrous ethanol, and filtered and dried to obtain chitosan acrylate.

[0029] The reaction mechanism of lignin, cellulose, chitin and acryloyl chloride is the same, that is, the hydroxyl group reacts with acryloyl chloride.

[0030] The present invention also protects the application of the above-mentioned regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt. After application, it can not only play the role of reinforcement and toughening, but also utilize the latent heat characteristics of the phase change fiber to absorb or release heat under corresponding environmental conditions, and adjust the temperature of the environment, thereby further improving the temperature stability of the asphalt.

[0031] Preferably, the application method is: heat 100 parts by weight of asphalt to a molten state, add 0.1-0.5 parts by weight of dried phase change fibers thereto, and prepare the phase change fiber modified asphalt by dispersing first and then shearing to ensure that the phase change fibers are fully dispersed in the matrix asphalt; the rotation speed in the dispersion stage is 400-600rpm, the temperature is 170-175℃, and the dispersion is 1-2h; the rotation speed in the shearing stage is 4000-5000rpm, the temperature is 170-180℃, and the shear is 1-3h; and cool at room temperature to obtain regenerated natural polymer-based solid-solid phase change fiber modified asphalt.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present application provides a regenerated natural polymer-based solid-solid phase change fiber, and applies the phase change fiber in asphalt to obtain phase change fiber-modified asphalt. In addition to the blocking, reinforcement and toughening effects, the phase change fiber can also give play to the unique advantages of phase change materials, actively regulate the use temperature of asphalt, reduce temperature diseases of asphalt pavement, and improve road performance and durability.

[0034] 2. In order to obtain spinning fibers, natural polymer-based solid-solid phase change materials should be able to be dissolved by imidazole-type ionic liquids. Therefore, cross-linking should not occur in the structure of natural polymer-based solid-solid phase change materials. Once cross-linking occurs, imidazole-type ionic liquids cannot dissolve it, and spinning fibers cannot be obtained. Based on this, in the process of preparing phase change fibers, this application uses polyethylene glycol monomethyl ether methacrylate (OEGMA) and octadecyl acrylate (A18) as raw materials. Polyethylene glycol monomethyl ether methacrylate (OEGMA) and octadecyl acrylate (A18) only have a single functional group that can be grafted with the hydroxyl group on the natural polymer material. During the reaction, each molecule can only generate one side chain group, thereby avoiding cross-linking at both ends, and finally forming a comb-like polymer that can be dissolved in imidazole-type ionic liquids for easy spinning. Similarly, when monofunctional modified polyethylene glycol (mPEG-OH, mPEG-CHO, mPEG-CNO, the terminal functional groups are hydroxyl, aldehyde, and isocyanate, respectively, polyethylene glycol monomethyl ether methacrylate is different from these three, and its terminal functional group is acrylate) is grafted with chitosan, only one functional group can react with the hydroxyl or amino group of chitosan to avoid the formation of cross-linked polymers.

[0035] 3. The present invention uses cellulose, chitosan, lignin or chitosan as raw materials. The natural polymer materials of cellulose, chitosan, lignin and chitosan used are abundant in nature and widely distributed. They have excellent biocompatibility and can be degraded by organisms such as microorganisms and enzymes without causing pollution to the environment. Moreover, they can be regenerated through planting, breeding and the like, and are sustainable and environmentally friendly.

[0036] 4. The regenerated natural polymer-based solid-solid phase change fiber prepared by the present invention has excellent dispersibility, so that the phase change fiber can fully exert its reinforcing effect while improving the storage stability of asphalt and reducing short-term aging.

[0037] 5. Regenerated natural polymer-based solid-solid phase change fiber can control the temperature of asphalt, so the design requirements for asphalt temperature stability can be appropriately reduced, saving asphalt material costs and reducing project costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The chemical reaction formula for the modification of cellulose, lignin and chitin;

[0039] Figure 2 This is a schematic diagram of the comb-like structure of the polyethylene glycol / cellulose-based solid-solid phase change material of Example 1;

[0040] Figure 3 Spinning flow chart for preparing regenerated natural polymer-based solid-solid phase change fibers. DETAILED DESCRIPTION

[0041] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0042] 1. The phase change fiber modified asphalt of the present invention is mixed with a phase change material with latent heat properties, which can give play to the unique advantages of its phase change function, that is, when the ambient temperature reaches the phase change temperature, the phase change material will undergo a change in physical state or crystal structure, accompanied by the absorption or release of energy, actively adjusting the ambient temperature, thereby improving the temperature stability of the asphalt.

[0043] The principle of the present invention to improve the temperature stability of asphalt is as follows: after the phase change fiber is added to the asphalt, the phase change fiber has excellent heat storage and heat release performance. When the temperature of the asphalt rises to the temperature of the phase change material, the phase change material undergoes phase transformation, absorbs and stores a large amount of heat, improves the high temperature stability and durability of the asphalt and the asphalt mixture, and can reduce the high temperature rutting disease of the road surface while improving the road performance. When the ambient temperature drops to its phase change temperature, the phase change fiber releases a large amount of heat, which can improve the road surface's resistance to low temperatures, improve low temperature stability, and reduce low temperature cracks. The presence of the phase change fiber keeps the temperature of the asphalt within a good working range, reduces the temperature change rate, thereby reducing the impact of temperature on the asphalt, reducing the temperature disease of the asphalt pavement, having good road performance for a long time, and extending the service life.

[0044] 2. Compared with base asphalt, modified asphalt mixed with phase change fiber can further reduce temperature sensitivity, reduce the influence of temperature on asphalt, and improve the working performance of asphalt. There will be physical action between fiber and asphalt. The fiber crisscrosses and firmly combines the asphalt, reducing the free asphalt, thereby increasing the overall viscosity and softening point, and improving the temperature stability of asphalt. After testing, compared with base asphalt, the softening point of regenerated natural polymer-based solid-solid phase change fiber modified asphalt is improved, which can effectively improve the segregation problem of asphalt and reduce the short-term aging phenomenon of asphalt.

[0045] The heating speed of phase-change fiber modified asphalt is slower than that of base asphalt. Within a certain range, as the amount of phase-change fiber increases, the heat storage and temperature regulation effect becomes more obvious. Therefore, the phase-change fiber modified asphalt of the present invention has good temperature regulation performance, can effectively control the temperature of asphalt pavement, reduce asphalt pavement diseases, improve pavement performance, and ultimately extend the service life of asphalt pavement. It can also improve the storage stability of asphalt and reduce short-term aging. After promotion, it will create economic value and play a huge social benefit.

[0046] The solution spinning methods of the embodiments of the present invention are all as follows: the mass fraction of the spinning solution is controlled to be 15%-20%, and then the spinning solution is sprayed out from a fine pinhole and solidified in hot air.

[0047] The technical solution is further described by using embodiments below, which are as follows:

[0048] The target materials of Examples 1-2 of the present invention are all polyethylene glycol / cellulose-based phase change fibers, and all use cellulose acrylate as raw material. The cellulose acrylate is prepared according to the following steps:

[0049] Take 1g of cellulose and add 50mL of solvent N,N , Dimethylacetamide (DMAC) and 10 mL of acryloyl chloride (AC), stirred for 5 h, washed and soaked with anhydrous ethanol after the reaction, and filtered and dried to obtain cellulose acrylate.

[0050] Example 1

[0051] The preparation method of polyethylene glycol / cellulose-based phase change fiber comprises the following steps:

[0052] (1) Dissolve 0.1 parts of cellulose acrylate, 0.6 parts of polyethylene glycol monomethyl ether methacrylate (OEGMA) and 0.7 parts of octadecyl acrylate (A18) in 5 mL of anhydrous DMAC by weight, freeze with liquid nitrogen and replace with N2 three times, add 0.06 parts of initiator benzoyl peroxide (BPO) and seal, stir at 65° C. for 24 h, filter, wash and dry to obtain a polyethylene glycol / cellulose-based solid-solid phase change material;

[0053] (2) dissolving the polyethylene glycol / cellulose-based solid-solid phase change material obtained in step (1) in 1-butyl 3-methylimidazolium chloride ionic liquid to obtain a spinning solution, spinning the spinning solution into fibers by a solution spinning method, and vacuum drying the fibers at 100° C. to obtain dry polyethylene glycol / cellulose-based phase change fibers.

[0054] Example 2

[0055] The preparation method of polyethylene glycol / cellulose-based phase change fiber comprises the following steps:

[0056] (1) Dissolve 0.2 parts of cellulose acrylate, 0.8 parts of polyethylene glycol monomethyl ether methacrylate (OEGMA) and 0.9 parts of octadecyl acrylate (A18) in 5 mL of anhydrous DMAC by weight, freeze with liquid nitrogen and replace with N2 three times, add 0.06 parts of initiator benzoyl peroxide (BPO) and seal, stir at 65° C. for 24 h, filter, wash and dry to obtain a polyethylene glycol / cellulose-based solid-solid phase change material;

[0057] (2) dissolving the polyethylene glycol / cellulose-based solid-solid phase change material obtained in step (1) in 1-butyl 3-methylimidazolium chloride ionic liquid to obtain a spinning solution, spinning the spinning solution into fibers by a solution spinning method, and vacuum drying the fibers at 100° C. to obtain dry polyethylene glycol / cellulose-based phase change fibers.

[0058] The target materials of Examples 3-4 of the present invention are all polyethylene glycol / chitosan-based phase change fibers, and all use chitosan acetic acid solution as a raw material. The chitosan acetic acid solution is prepared according to the following steps:

[0059] Take 0.25g of chitosan and add it to a 0.5% acetic acid solution by volume, stir it in a 25°C water bath for 2h, ultrasonically treat the mixed solution for 30min to remove bubbles generated during the stirring process, and then let it stand for 1h to obtain a uniform and stable chitosan acetic acid solution with a concentration of 0.025g / mL.

[0060] Example 3

[0061] The preparation method of polyethylene glycol / chitosan-based phase change fiber comprises the following steps:

[0062] (1) Add 1 part of PEG-OH to 5 parts of chitosan acetic acid solution with a concentration of 0.025 g / mL, stir evenly, then drop 2 mL of glutaraldehyde, let stand for 6 hours and then dry to obtain a polyethylene glycol / chitosan-based solid-solid phase change material;

[0063] (2) dissolving the polyethylene glycol / chitosan-based solid-solid phase change material obtained in step (1) in 1-butyl 3-methylimidazolium chloride ionic liquid to obtain a spinning solution, spinning the spinning solution into fibers by a solution spinning method, and vacuum drying at 100° C. to obtain dry polyethylene glycol / chitosan-based phase change fibers.

[0064] Example 4

[0065] The preparation method of polyethylene glycol / chitosan-based phase change fiber comprises the following steps:

[0066] (1) 1.2 parts of PEG-CHO were added to 5 parts of chitosan acetic acid solution with a concentration of 0.025 g / mL, and 2 mL of glutaraldehyde was added dropwise after stirring. The mixture was allowed to stand for 6 hours and then dried to obtain a polyethylene glycol / chitosan-based solid-solid phase change material;

[0067] (2) dissolving the polyethylene glycol / chitosan-based solid-solid phase change material obtained in step (1) in 1-butyl 3-methylimidazolium chloride ionic liquid to obtain a spinning solution, spinning the spinning solution into fibers by a solution spinning method, and vacuum drying at 100° C. to obtain dry polyethylene glycol / chitosan-based phase change fibers.

[0068] The target materials of Examples 5-6 of the present invention are all polyethylene glycol / lignin-based phase change fibers, and all use lignin acrylate as raw material. The lignin acrylate is prepared according to the following steps:

[0069] Take 1g of lignin, add 50mL of solvent N,N-dimethylacetamide (DMAC) and 10mL of acryloyl chloride (AC), stir for 5h, wash and soak with anhydrous ethanol after the reaction, and filter and dry to obtain lignin acrylate.

[0070] Example 5

[0071] The preparation method of polyethylene glycol / lignin-based phase change fiber comprises the following steps:

[0072] (1) By mass fraction, 0.1 parts of lignin acrylate, 0.6 parts of polyethylene glycol monomethyl ether methacrylate (OEGMA) and 0.7 parts of octadecyl acrylate (A18) were dissolved in 5 mL of anhydrous DMAC, and after three times of liquid nitrogen freezing and N2 replacement, 0.06 parts of initiator benzoyl peroxide (BPO) were added and sealed, and after stirring at 65° C. for 24 hours, the mixture was filtered, washed and dried to obtain a polyethylene glycol / lignin-based solid-solid phase change material;

[0073] (2) dissolving the polyethylene glycol / lignin-based solid-solid phase change material obtained in step (1) in 1-butyl 3-methylimidazolium chloride ionic liquid to obtain a spinning solution, spinning the spinning solution into fibers by a solution spinning method, and vacuum drying at 100° C. to obtain dry polyethylene glycol / lignin-based phase change fibers.

[0074] Example 6

[0075] The preparation method of polyethylene glycol / lignin-based phase change fiber comprises the following steps:

[0076] (1) By mass fraction, 0.2 parts of lignin acrylate, 0.8 parts of polyethylene glycol monomethyl ether methacrylate (OEGMA) and 0.9 parts of octadecyl acrylate (A18) were dissolved in 5 mL of anhydrous DMAC, and after three times of liquid nitrogen freezing and N2 replacement, 0.06 parts of initiator benzoyl peroxide (BPO) were added and sealed, and after stirring at 65° C. for 24 hours, the mixture was filtered, washed and dried to obtain a polyethylene glycol / lignin-based solid-solid phase change material;

[0077] (2) dissolving the polyethylene glycol / lignin-based solid-solid phase change material obtained in step (1) in 1-butyl 3-methylimidazolium chloride ionic liquid to obtain a spinning solution, spinning the spinning solution into fibers by a solution spinning method, and vacuum drying at 100° C. to obtain dry polyethylene glycol / lignin-based phase change fibers.

[0078] The target materials of Examples 7-8 of the present invention are all polyethylene glycol / chitin-based phase change fibers, and all use chitosan acrylate as a raw material. The chitosan acrylate is prepared according to the following steps:

[0079] Take 1g of chitosan, add 50mL of solvent N,N-dimethylacetamide (DMAC) and 10mL of acryloyl chloride (AC), stir for 5h, wash and soak with anhydrous ethanol after the reaction, and filter and dry to obtain chitosan acrylate.

[0080] Example 7

[0081] The preparation method of polyethylene glycol / chitin-based solid-solid phase change material comprises the following steps:

[0082] (1) By mass fraction, 0.1 parts of chitosan acrylate, 0.6 parts of polyethylene glycol monomethyl ether methacrylate (OEGMA) and 0.7 parts of octadecyl acrylate (A18) were dissolved in 5 mL of anhydrous DMAC, and after three times of liquid nitrogen freezing and N2 replacement, 0.06 parts of initiator benzoyl peroxide (BPO) were added and sealed, and after stirring at 65° C. for 24 hours, the mixture was filtered, washed and dried to obtain a polyethylene glycol / chitosan-based solid-solid phase change material;

[0083] (2) dissolving the polyethylene glycol / chitin-based solid-solid phase change material obtained in step (1) in 1-butyl 3-methylimidazolium chloride ionic liquid to obtain a spinning solution, spinning the spinning solution into fibers by a solution spinning method, and vacuum drying at 100° C. to obtain dry polyethylene glycol / chitin-based phase change fibers.

[0084] Example 8

[0085] The preparation method of polyethylene glycol / chitin-based solid-solid phase change material comprises the following steps:

[0086] (1) By mass fraction, 0.2 parts of chitosan acrylate, 0.8 parts of polyethylene glycol monomethyl ether methacrylate (OEGMA) and 0.9 parts of octadecyl acrylate (A18) were dissolved in 5 mL of anhydrous DMAC, and after three times of liquid nitrogen freezing and N2 replacement, 0.06 parts of initiator benzoyl peroxide (BPO) were added and sealed, and after stirring at 65° C. for 24 hours, the mixture was filtered, washed and dried to obtain a polyethylene glycol / chitosan-based solid-solid phase change material;

[0087] (2) dissolving the polyethylene glycol / chitin-based solid-solid phase change material obtained in step (1) in 1-butyl 3-methylimidazolium chloride ionic liquid to obtain a spinning solution, spinning the spinning solution into fibers by a solution spinning method, and vacuum drying at 100° C. to obtain dry polyethylene glycol / chitin-based phase change fibers.

[0088] The present invention also provides the application of regenerated natural polymer-based solid-solid phase change fiber, specifically using regenerated natural polymer-based solid-solid phase change fiber to modify asphalt, and the ratio of the two, calculated by mass, is: 100 parts of base asphalt to 0.1-0.5 parts of regenerated natural polymer-based solid-solid phase change fiber.

[0089] The temperature regulating performance of the natural polymer-based solid-solid phase change fiber modified asphalt prepared by the present invention was also tested. The temperature regulating performance test method is: prepare equal masses of phase change fiber modified asphalt and 70# matrix asphalt standard test pieces respectively, bury the temperature sensor in the asphalt, and then raise and lower the temperature of the two at the same time, observe and record their temperature changes. Among them, when heating up, put the phase change fiber modified asphalt and the same mass of 70# matrix asphalt into a 60°C water bath; when cooling down, put the phase change fiber modified asphalt and the same mass of 70# matrix asphalt into an ice-water mixture with a volume ratio of 1:1. The test results are shown in Table 1:

[0090] The polyethylene glycol / cellulose-based phase change fiber of Example 1 was used as a raw material, 0.3 parts of the polyethylene glycol / cellulose-based phase change fiber was added to 100 parts of the matrix asphalt heated to a molten state, and the modified asphalt was prepared by first dispersing and then shearing; the speed of the dispersion stage was 500 rpm, the temperature was 170°C, and the dispersion was performed for 1 hour; the speed of the shearing stage was 4500 rpm, the temperature was 175°C, and the shearing was performed for 2 hours, and the polyethylene glycol / cellulose-based phase change fiber modified asphalt was obtained by cooling at room temperature;

[0091] It has been verified that when the temperature of the recycled natural polymer-based solid-solid phase change fiber modified asphalt rises, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 8.6°C; when the temperature drops, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 4.0°C.

[0092] Using the polyethylene glycol / cellulose-based phase change fiber of Example 2 as a raw material, 0.4 parts of the polyethylene glycol / cellulose-based phase change fiber were added to 100 parts of the matrix asphalt heated to a molten state, and the modified asphalt was prepared by first dispersing and then shearing; the speed of the dispersion stage was 500 rpm, the temperature was 170°C, and the dispersion was performed for 1 hour; the speed of the shearing stage was 4500 rpm, the temperature was 175°C, and the shearing was performed for 2 hours, and the polyethylene glycol / cellulose-based phase change fiber modified asphalt was obtained by cooling at room temperature;

[0093] It has been verified that when the temperature of the recycled natural polymer-based solid-solid phase change fiber modified asphalt rises, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 8.8°C; when the temperature drops, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 4.1°C.

[0094] Using the polyethylene glycol / chitosan-based phase change fiber of Example 3 as a raw material, 0.3 parts of the polyethylene glycol / chitosan-based phase change fiber was added to 100 parts of the matrix asphalt heated to a molten state, and the modified asphalt was prepared by first dispersing and then shearing; the speed of the dispersion stage was 500 rpm, the temperature was 170°C, and the dispersion was performed for 1 hour; the speed of the shearing stage was 4500 rpm, the temperature was 175°C, and the shearing was performed for 2 hours, and the polyethylene glycol / chitosan-based phase change fiber modified asphalt was obtained by cooling at room temperature;

[0095] It has been verified that when the temperature of the recycled natural polymer-based solid-solid phase change fiber modified asphalt rises, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 8.7°C; when the temperature drops, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 3.7°C.

[0096] Using the polyethylene glycol / chitosan-based phase change fiber of Example 4 as a raw material, 0.4 parts of the polyethylene glycol / chitosan-based phase change fiber were added to 100 parts of the matrix asphalt heated to a molten state, and the modified asphalt was prepared by first dispersing and then shearing; the speed of the dispersion stage was 500 rpm, the temperature was 170°C, and the dispersion was performed for 1 hour; the speed of the shearing stage was 4500 rpm, the temperature was 175°C, and the shearing was performed for 2 hours, and the polyethylene glycol / chitosan-based phase change fiber modified asphalt was obtained by cooling at room temperature;

[0097] It has been verified that when the temperature of the recycled natural polymer-based solid-solid phase change fiber modified asphalt rises, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 9.2°C; when the temperature drops, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 3.9°C.

[0098] Using the polyethylene glycol / lignin-based phase change fiber of Example 5 as a raw material, 0.3 parts of the polyethylene glycol / lignin-based phase change fiber was added to 100 parts of the matrix asphalt heated to a molten state, and the modified asphalt was prepared by first dispersing and then shearing; the speed of the dispersion stage was 500 rpm, the temperature was 170°C, and the dispersion was performed for 1 hour; the speed of the shearing stage was 4500 rpm, the temperature was 175°C, and the shearing was performed for 2 hours, and the polyethylene glycol / lignin-based phase change fiber modified asphalt was obtained by cooling at room temperature;

[0099] It has been verified that when the temperature of the recycled natural polymer-based solid-solid phase change fiber modified asphalt rises, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 8.5°C; when the temperature drops, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 4.1°C.

[0100] Using the polyethylene glycol / lignin-based phase change fiber of Example 6 as a raw material, 0.4 parts of the polyethylene glycol / lignin-based phase change fiber were added to 100 parts of the matrix asphalt heated to a molten state, and the modified asphalt was prepared by first dispersing and then shearing; the speed of the dispersion stage was 500 rpm, the temperature was 170°C, and the dispersion was performed for 1 hour; the speed of the shearing stage was 4500 rpm, the temperature was 175°C, and the shearing was performed for 2 hours, and the polyethylene glycol / lignin-based phase change fiber modified asphalt was obtained by cooling at room temperature;

[0101] It has been verified that when the temperature of the recycled natural polymer-based solid-solid phase change fiber modified asphalt rises, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 9.0°C; when the temperature drops, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 4.5°C.

[0102] Using the polyethylene glycol / chitin-based phase change fiber of Example 7 as a raw material, 0.3 parts of the polyethylene glycol / chitin-based phase change fiber were added to 100 parts of the matrix asphalt heated to a molten state, and the modified asphalt was prepared by first dispersing and then shearing; the speed of the dispersion stage was 500 rpm, the temperature was 170°C, and the dispersion was performed for 1 hour; the speed of the shearing stage was 4500 rpm, the temperature was 175°C, and the shearing was performed for 2 hours, and the polyethylene glycol / chitin-based phase change fiber modified asphalt was obtained by cooling at room temperature;

[0103] It has been verified that when the temperature of the recycled natural polymer-based solid-solid phase change fiber modified asphalt rises, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 8.9°C; when the temperature drops, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 3.8°C.

[0104] Using the polyethylene glycol / chitin-based phase change fiber of Example 8 as a raw material, 0.4 parts of the polyethylene glycol / chitin-based phase change fiber were added to 100 parts of the matrix asphalt heated to a molten state, and the modified asphalt was prepared by first dispersing and then shearing; the speed of the dispersion stage was 500 rpm, the temperature was 170°C, and the dispersion was performed for 1 hour; the speed of the shearing stage was 4500 rpm, the temperature was 175°C, and the shearing was performed for 2 hours, and the polyethylene glycol / chitin-based phase change fiber modified asphalt was obtained by cooling at room temperature;

[0105] It has been verified that when the temperature of the recycled natural polymer-based solid-solid phase change fiber modified asphalt rises, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 9.1°C; when the temperature drops, the absolute temperature difference between it and the existing matrix asphalt (70# matrix asphalt) specimen of equal mass is 4.2°C.

[0106] Table 1 Test results of temperature control performance of recycled natural polymer-based solid-solid phase change fiber modified asphalt

[0107]

[0108]

[0109] It can be seen that the modified asphalt with the addition of recycled natural polymer-based solid-solid phase change fiber is less affected by the external temperature: when the external temperature is high, its temperature rises slowly, and when the external temperature is low, its temperature decreases slowly, indicating that the recycled natural polymer-based solid-solid phase change fiber plays a certain role in temperature regulation and can improve the temperature stability of asphalt to a certain extent. For the same modified asphalt, as the amount of recycled natural polymer-based solid-solid phase change fiber increases, the greater the temperature difference between it and the matrix asphalt, the better the temperature regulation performance; for different modified asphalts, the temperature regulation performance is not much different. In addition, the temperature difference of the phase change fiber modified asphalt during the heating process is generally higher than the temperature difference during the cooling process, indicating that compared with low-temperature stability, it has more advantages in improving high-temperature stability.

[0110] Table 2 Test results of softening point of regenerated natural polymer-based solid-solid phase change fiber modified asphalt

[0111]

[0112] It can be seen that the softening point of the modified asphalt added with recycled natural polymer-based solid-solid phase change fiber is higher than that of the base asphalt, and within a certain range, the softening point also increases with the increase of fiber content. The increase in softening point means that the high-temperature stability of the asphalt is better and the aging phenomenon can be reduced.

[0113] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.

Claims

1. An application of a regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt, characterized in that: Based on natural polymer materials, the hydroxyl groups on the natural polymer materials are chemically grafted with phase change materials to obtain natural polymer-based solid-solid phase change materials, and then the natural polymer-based solid-solid phase change materials are spun by solution spinning to obtain regenerated natural polymer-based solid-solid phase change fibers; The phase change material is a phase change material having a single functional group; Wherein, the monofunctional phase change material is selected from one or more of modified polyethylene glycol, octadecyl acrylate, homologues of octadecyl acrylate, octadecylamine, and oleylamine; 100 parts by weight of asphalt are heated to a molten state, and 0.1-0.5 parts by weight of dried regenerated natural polymer-based solid-solid phase change fiber is added thereto, and the phase change fiber-modified asphalt is prepared by a method of first dispersing and then shearing; The natural polymer material is selected from cellulose, chitosan, lignin or chitin.

2. The use of the regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt according to claim 1, characterized in that: The modified polyethylene glycol is selected from polyethylene glycol monomethyl ether methacrylate, methoxy polyethylene glycol-hydroxy, methoxy polyethylene glycol-aldehyde or methoxy polyethylene glycol isocyanate.

3. The use of the regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt according to claim 1, characterized in that: The natural polymer-based solid-solid phase change material is a comb-structured polymer, and the natural polymer-based solid-solid phase change material can be dissolved by imidazole-type ionic liquid.

4. The use of the regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt according to claim 1, characterized in that: The natural polymer-based solid-solid phase change material is prepared according to the following steps: The cellulose, lignin or chitin are modified respectively to obtain a treated natural polymer material I; The treated natural polymer material I, phase change material and initiator are mixed, and then a free radical polymerization reaction is carried out under completely anaerobic conditions, so that the phase change material is grafted onto the treated natural polymer material I to obtain a natural polymer-based solid-solid phase change material I.

5. The use of the regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt according to claim 4, characterized in that: The mass ratio of the treated natural polymer material I, the phase change material and the initiator is 0.1-0.2:1-2:0.

06.

6. The use of the regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt according to claim 1, characterized in that: The natural polymer-based solid-solid phase change material is prepared according to the following steps: The chitosan is modified to obtain a processed natural polymer material II; The treated natural polymer material II, phase change material and glutaraldehyde are mixed, left to stand for 5-7 hours and then dried to obtain the natural polymer-based solid-solid phase change material II.

7. The use of the regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt according to claim 6, characterized in that: The ratio of the treated natural polymer material II, the phase change material and glutaraldehyde is 1-1.2 g: 5-10 g: 1-2 mL, and the treated natural polymer material II is 0.025 g / mL.

8. The use of the regenerated natural polymer-based solid-solid phase change fiber in the preparation of phase change fiber modified asphalt according to claim 4 or 6, characterized in that: Regenerated natural polymer-based solid-solid phase change fibers are prepared according to the following steps: The natural polymer-based solid-solid phase change material I or the natural polymer-based solid-solid phase change material II is dissolved in an imidazole-type ionic liquid, and then electrostatic spinning is performed to obtain a regenerated natural polymer-based solid-solid phase change fiber.

Citation Information

Patent Citations

  • Solid-solid phase change material based on cellulose acrylate and preparation method of solid-solid phase change material

    CN108360080A

  • Chitosan-based composite fiber with function of phase-change temperature regulation and manufacturing method of chitosan-based composite fiber

    CN110863261A